Acousto-optic modulators for fibre-optic lines. (October 2020) - Epikhin, V.M.; Karnaushkin, P.V.
Abstract: The specific features of efficient matching of acousto-optic devices with single-mode fibres for the cases of isotropic and anisotropic diffraction are considered. The acousto-optic interaction geometry, optimal for modulating an arbitrarily polarised light beam with a possibility of tuning its frequency shift in the range up to ∼10 MHz, is chosen. Acousto-optic modulators/frequency shifters based on paratellurite (TeO2 ), pigtailed with polarisation-maintaining and non-polarisation-maintaining fibres, have been developed for wavelengths of 1064 and 1550 nm, and their main technical parameters are investigated.